Ontological statute of the human embryo as a person. A perspective from biological research in Latin America - Olivo Yépez, Álvaro; Linares Márquez, Pascual; Suárez Guerrero, Ana Isabel; Aguirre Guzmán, Ana María (Acta Bioethica, 2016)
The utilization of human embryos in the biological research has generated a bioethical debate from the ontological point of view about whether or not to consider the embryo as a human person. This paper review the ontological statute of the human embryo from a biological perspective considering the principal lines of investigation in Latin America. Complementary to discussion we check the contribution from the legal statute of the human embryo and the position from the formal scientific research in his utilization. Finally, we consider that, in Latin America, the discussion has not been approached in a deep way about the statute of the human embryo as person, staying the discussion in a dimension of the biological thing.